2006
DOI: 10.1016/j.jmva.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Bias correction of cross-validation criterion based on Kullback–Leibler information under a general condition

Abstract: This paper deals with the bias correction of the cross-validation (CV) criterion to estimate the predictive Kullback-Leibler information.A bias-corrected CV criterion is proposed by replacing the ordinary maximum likelihood estimator with the maximizer of the adjusted log-likelihood function. The adjustment is just slight and simple, but the improvement of the bias is remarkable. The bias of the ordinary CV criterion is O(n −1 ), but that of the bias-corrected CV criterion is O(n −2 ). We verify that our crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In this paper, two bias-corrected versions of K-fold crossvalidation are derived. The results can be seen as a generalization of the results of Yanagihara et al (2006).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…In this paper, two bias-corrected versions of K-fold crossvalidation are derived. The results can be seen as a generalization of the results of Yanagihara et al (2006).…”
Section: Introductionsupporting
confidence: 57%
“…Yanagihara et al (2006) considered bias correction of leave-one-out cross-validation when Ψ (z; θ) = − log p(z; θ). They showed that (1) and (2) are bias-corrected leave-one-out cross-validation estimates of the prediction error when λ = (2N) −1 + O(N −2 ).…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the distribution of u i is the same as that of y i and since Y and U are independent of each other, the following commutative equation, as in Yanagihara et al (2006), holds:…”
Section: A2 Decomposition Of E * [Press]mentioning
confidence: 99%